Unveiling Center‐Type Topological Defects on Rosettes of Lead Zirconate Titanate Associated to Oxygen Vacancies. Issue 2 (30th December 2021) - Neckel, Itamar T.; da Silva, Francisco M. C.; Guedes, Eduardo B.; Dias, Carlos S. B.; Soares, Marcio M.; Costa, Carlos A. R.; Mori, Thiago J. A.; Björling, Alexander; Zakharov, Alexei; Tolentino, Helio C. N.
Abstract: Understanding the formation of topological defects in ferroelectric materials can provide access to their unusual physics, invaluable for possible applications of domain engineering in nanoelectronics. The present study shows the spontaneous formation of center‐type topological defects in lead zirconate titanate (PZT) films, characterized by a strong in‐plane radial electromechanical response on rosette‐like structures, as revealed by piezoelectric response force microscopy. Multi‐modal electron and X‐ray based techniques provide a comprehensive set of tools for delving at atomic scale the local chemistry, electronic, and crystalline structures. The elemental surface‐sensitivity of soft X‐ray absorption shows chemical segregation and drastic changes in the titanium electronic structure, which have been associated to oxygen vacancies, leading to a mechanism that describe the polarization symmetry on the rosettes. X‐ray nanofluorescence experiments revealed titanium segregation, corroborating with the absorption and low energy electron microscopy images. Taking advantage of a nanobeam, 2D nanodiffraction maps probed the complex microstructure of the domains, revealing its mosaicity and lattice strain at the nanoscale. This study highlights a complex topological structure and provides, by the simultaneous application of a set of analytical tools, a broad comprehension of the formation of center‐type ferroelectric topological defects in PZT. Abstract : The fascinating physics present in ferroelectric domains have attracted great attention due to their applications in ferroelectric devices. This research article goes down to the nanoscale, taking advantage of the high sensitivity of advanced X‐ray based techniques to look closely the chemistry and structure exuberant radial vortex present in rosettes of lead zirconate titanate.